Book Review. (1st September 2018) - Coker, Cait
Fandom as Classroom Practice: A Teaching Guide, Katherine Anderson Howell (ed.) (2018)Iowa City: University of Iowa Press, 168 pp., ISBN 9781609385675, p/bk, $70.00